Coupling of Incl3-bails for catalytic conversion of oil palm biomass to levulinic acid and upgrading to ethyl levulinate biofuel - Tiong, Yong Wei (2019)
Biomass has emerged as an abundant and relatively low cost carbon resource alternative to fossil fuels in the sustainable production of specialty chemicals and biofuel. Levulinic acid is an attractive platform chemical which can be obtained from biomass. Upgrading of levulinic acid produces ethyl levulinate biofuel, which serve as a transportation fuel and a fuel additive. Herein, this study reports a new environmentally friendly coupling mixed acids ionic liquids catalytic system, i.e. indium trichloride-1-methylimidazolium hydrogen sulphate (InCl3-[HMIM][HSO4]), for the catalytic conversions of oil palm empty fruit bunch and mesocarp fibre biomass to levulinic acid and upgrading to ethyl levulinate. In this two-step sequential reaction, i.e. the depolymerisation to levulinic acid, followed by the upgrading esterification to ethyl levulinate, the optimum depolymerisation occurred at 177⁰C in 4.8 h with 0.15 mmol indium trichloride in ionic liquids-to-biomass ratio of 6.6:1 (w/w) and 22.7% (w/w) of water, whilst esterification was at 105⁰C in 12.2 h with ethanol to substrate ratio of 7.2:1 (v/v). The maximum levulinic acid yields were 17.7% and 18.4%, followed by subsequent upgrading ethyl levulinate yields of 18.7% and 20.1% from the conversions of oil palm empty fruit bunch and mesocarp fibre biomass, respectively. Levulinic acid and ethyl levulinate efficiencies were >63% for both biomass conversions. These results further suggested that InCl3-[HMIM][HSO4] catalytic system offers a better or comparable catalytic activity than other ionic liquids catalytic system for the biomass conversion to levulinic acid and upgrading to ethyl levulinate. Additionally, through kinetic and thermodynamic studies for the oil palm mesocarp fibre cellulose conversion to levulinic acid and upgrading to ethyl levulinate via InCl3-[HMIM][HSO4] catalytic system, relatively low activation energies of 56.5 kJ mol-1 and 28.1 kJ mol-1 were achieved for cellulose depolymerisation and the subsequent upgrading esterification, respectively. Meanwhile, the Gibbs free energy of activation for cellulose depolymerisation and the subsequent upgrading esterification were +115.5 kJ mol-1 and +90.3 kJ mol-1, respectively. These results were relatively lower than other catalytic systems, indicating that the present catalytic system was relatively more energetically and kinetically feasible. Finally, InCl3-[HMIM][HSO4] could be recycled up to three consecutive runs with a minimal loss of <25% ethyl levulinate yield. Hence, this would directly benefit the process development in terms of catalytic studies at pilot and industrial scales. Overall, this study highlighted the potential of novel coupling mixed acids InCl3-[HMIM][HSO4] catalytic system for biorefinery processing of oil palm empty fruit bunch and mesocarp fibre biomass to levulinic acid and upgrading to ethyl levulinate from a greener and more sustainable perspective.